(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The data on the shoot formation, types of buds, different age groups of plants and the peculiarities of the specialized and non-specialized vegetative reproduction are given in the article. Five stages of morphogenesis are shown. The features of spatial structure of individuals are described.